Ergonomic solutions for referee mistakes: A visual assessment of the environment in boxing competitions - Uca, M.; Ayvaz, E.; Yildiz, Z. (Perceptual and Motor Skills, 2025)
Background: This study examines whether transparent boxing ring ropes increase referees` visual access and improve scoring accuracy and consistency.